Diagnosis of access to gyneco-obstetrician health services for women inmates in prison establishments in Peru - Pezo Jimenez, Omar; Peñaloza de la Torre, Ulises Massino; Pezo Jimenez, Julissa Paola (Medicina Clínica y Social, 2023)
Introduction: It is transcendental to study access to health in various fields and especially in populations in a state of vulnerability. Female inmates are considered a special population group, as they are different from other populations in terms of their freedom of movement. This state of vulnerability generates problems, especially in access to health services for the detection, treatment and prevention of diseases. Objective: The objective of the study was to detect access to gynecologist-obstetric health services in penitentiary establishments in Peru during the year 2021. Method: The study is descriptive, longitudinal, was carried out in the penitentiary setting and covers all the penitentiary establishments in the regions of Peru with a female penitentiary population distributed throughout the Peruvian territory during the year 2021. For data collection, the the secondary source documentary technique, the instrument in which the information collected was lost was the documentary file. Results: It was found that 13 women’s prisons and 31 women’s pavilions, of which only 15 (34.09%) have gynecologist-obstetric service, while 29 (35.91%) do not have gynecologist-obstetric service. . Of the total prison population studied, 4,360 inmates, not all of them received at least one gynecologist-obstetrician care during the year 2021 Discussion: Access to gynecologist-obstetric services in the women’s prison population in Peru is restricted, placing women deprived of their liberty in a situation of vulnerability.